Part 1:
We factor the number 56. 56 = 2 * 2 * 2 * 7 when factored down to primes. We see the number two is repeated, so we can pair two of them to make a perfect square.
√56 = √(2 * 2) * √(2*7) = √4 * √14 = 2 * √14 = 2√14.
Part 2:
√-56 = √-1 * √56
By definition, √-1 = i, and by the first part of the problem √56 = 2√14. The i is not under a radical, so it goes with the whole part of the term, that is 2i√14.
2007-09-18 19:21:40
·
answer #1
·
answered by James 5
·
0⤊
1⤋
You are correct in factoring 56 into 7 x 8. But you made a little mistake, you forgot the other factor :)
√56 = √(7 x 8) = √7 x √8 = √7 x 2√2
Since we have the same index (both are square roots) we have:
√7 x 2√2 = 2√14, which is the simplest form of √56
2007-09-18 18:57:04
·
answer #2
·
answered by tangy 5
·
0⤊
0⤋
yes, you can make it either a mixed number by seeing how many times 36 can go into 56 (once only), and then take 36 away from 56 which will give you 20. so then you have 1 20/36, which you then can divide four by the numerator (56) and the denominator (36) which will give you 1 5/9 or you can make it an improper fraction by diving both the numerator (56) and the denominator (36) by four which will give you 14/9 hope this helped (:
2016-05-18 02:55:15
·
answer #3
·
answered by ? 3
·
0⤊
0⤋
Question 1
√ 56 = √( 4 x 14 ) = 2√14
Question 2
√( - 56 ) = √( 56 i ² ) = (2√14) i
but i (2√14) is acceptable also.
2007-09-18 22:52:00
·
answer #4
·
answered by Como 7
·
1⤊
0⤋
Lisa Dear,
What you wrote is incorrect.
But here is something you can do:
Try to think:
mmm... 56 = 2*28, 7*8, 4*14 -> AHA
4 has a whole square root so you can say:
sqrt(56) = sqrt(4) * sqrt(14) = 2*sqrt(14)
I don't know what can be done further than that.
2007-09-18 18:58:18
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
???
√7 * √8 = 2√2 ??? Not in my world it doesn't ☺
√56 = √(8*7) = 2√(2*7) = 2√14
Doug
2007-09-18 18:59:24
·
answer #6
·
answered by doug_donaghue 7
·
0⤊
0⤋
2√14
u got the √7 x 2√2 because 2√2 =√8
then u would just multiply the √7 and √2 which gives u √14
and ur final answer would be 2.√14
Hoped this helped =)
2007-09-18 18:57:13
·
answer #7
·
answered by laze-butt 3
·
1⤊
0⤋
2√14. You factored it as much as you can. Now all you can do is multiply the roots.
2007-09-18 18:55:58
·
answer #8
·
answered by Matiego 3
·
0⤊
0⤋
sqr(56) = sqr(4 x 14) = 2(sqr(14)) that's about as reduced as you can get.
2007-09-18 18:56:32
·
answer #9
·
answered by merlot7799 3
·
0⤊
0⤋
sqrt(56)=sqrt(4*14)=sqrt(4)*sqrt(14)=2sqrt(14)
sqrt(7)*sqrt(8)=sqrt(7)*2sqrt(2)=2sqrt(7*2)=2sqrt(14)
because sqrt(8)=2sqrt(2)
2007-09-18 19:00:44
·
answer #10
·
answered by tootoot 3
·
0⤊
0⤋